The Cost of Social Security: Basic Tables (International Labour Office, 1995)
Fourteenth international inquiry 1987-1989. The basic tables giving detailed information on a disaggregated basis on the financial operations of all the social security schemes in the listed countries.
Keywords: ILO collection-Social security-Nonfiction